1968
DOI: 10.1104/pp.43.3.345
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Water Uptake in Sugar Beet Roots by Ammonia

Abstract: Abstract. Ammonium sulfate, ammonium carbonate or ammonia gas inhibited water uptake in sugar beet roots whenever the pH was sufficiently high to cause the production of ammonia. When ammonia was removed by aeration, inhibition of the water uptake by roots was rapidly reversed. ATP at 0.2 mm appeared to either wholly or partially prevent the ammon,ia-induced inhibition of water uptake by roots. ATP may be involved in maintaining the structure of water pathways through the root. In roots lacking epidermis, ammo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
14
0

Year Published

1969
1969
2011
2011

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 21 publications
0
14
0
Order By: Relevance
“…Stuart and Haddock (4) indicated that the inhibiting effect of NH4+ on sugar beet roots occurs only when the pH is sufficiently high (above 7) to cause the production of NH,. It would appear, however, that in our experiments the inhibition of water uptake is a result of NH4+ rather than NH.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Stuart and Haddock (4) indicated that the inhibiting effect of NH4+ on sugar beet roots occurs only when the pH is sufficiently high (above 7) to cause the production of NH,. It would appear, however, that in our experiments the inhibition of water uptake is a result of NH4+ rather than NH.…”
Section: Discussionmentioning
confidence: 99%
“…This observation suggested that ammonium interferes with the absorption or movement of water in the tomato plant. Recent studies by Stuart and Haddock (4) with excised sugar beet roots indicate that ammonia inhibits water uptake. In this study we attempted to determine if ammonium (NH,) in solution culture would have a similar effect on tomato.…”
mentioning
confidence: 99%
“…One of the primary consequences of respiration is the formation of ATP, which is used as a source of energy in many intracellular reactions. Stuart and Haddock (25) found that sugar beet roots, pretreated with ATP, did not exhibit as much reduced water permeability when a respiration inhibitor, ammonia (30,31) Uniform disks, 14 mm in diameter and 1 mm thick, were cut from potato tubers (Solanum tuberosum L. var. Russet).…”
mentioning
confidence: 99%
“…Respiration inhibitors and uncouplers such as ammonia (25), azide (15,20,27), cyanide (3,16,18,27,28), carbonyl cyanide m-chlorophenylhydrazone (1, 3), 2,4-dinitrophenol (18,32), fluoride (27,32), iodoacetate (27,32), arsenate (27), CO, (5,12), lack of oxygen (12,21), and low temperatures (13) decrease the movement of water into or out of coleoptile segments, radicles, root segments, or whole roots.…”
mentioning
confidence: 99%
“…Prange (1980) Quebedaux and Osbun (1973) and Pill and Lambeth (19'7'7). and not ammonia gas as suggested by Stuart and Haddock (1968). A measurable amount of free ammonium in a plant tissue can signify the onset of ammonium toxicity (Reisenauer 1978;Ikeda andOsawa 1979, 1980 (Quebedaux and Osbun 19'73;Plll andLambeth 1977, 1980).…”
mentioning
confidence: 99%